Heavy metal concentrations in Brazilian port areas and their relationships with microorganisms: can pollution in these areas change the microbial community? - Zampieri, Bruna Del Busso [UNESP]; da Costa Andrade, Vanessa [UNESP]; Chinellato, Roberta Merguizo [UNESP]; Garcia, Carlos Alexandre Borges; de Oliveira, Marcos Antônio [UNESP]; Brucha, Gunther; de Oliveira, Ana Julia Fernandes Cardoso [UNESP] (Springer Nature, 2020)
The objectives of this study were to analyze the difference in ways in which metals polluting Brazilian port areas influence bacterial communities and the selection of resistant strains. The hypothesis tested was that port areas would have microbial communities significantly different from a pristine area, mainly due to a greater load of metals found in these areas. Sediment samples were collected in two port areas (Santos and São Sebastião) and one pristine area (Ubatuba). Total DNA was extracted and MiSeq sequencing was performed. A hundred strains were isolated from the same samples and were tested for metal resistance. The community composition was similar in the two port regions, but differed from the pristine area. Microbial diversity was significantly lower in the port areas. The phyla Proteobacteria, Cyanobacteria, and Thermodesulfobacteria exhibited positive correlations with copper and zinc concentrations. Chloroflex, Nitrospirae, Planctomycetes, and Chlorobi exhibited negative correlations with copper, chromium, and zinc. Cr and Zn had higher concentrations at port areas and were responsible to select more metal-resistant strains. Some genera were found to be able to easily develop metal resistance. The most isolated genera were Bacillus, Vibrio, and Pseudomonas. This type of study can illustrate, even in very complex natural environments, the influence of pollution on the community as a whole and the consequences of these changes.
Keywords: Bacteria community; Coastal areas; Contaminants; Metals; Microbial diversity